2023
DOI: 10.1039/d2ob02235d
|View full text |Cite
|
Sign up to set email alerts
|

Glycocalix[4]arenes and their affinity to a library of galectins: the linker matters

Abstract: Galectins are lectins that bind β-galactosides. They are involved in important extra- and intracellular biological processes such as apoptosis, and regulation of the immune system or the cell cycle. High-affinity...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 44 publications
3
17
0
Order By: Relevance
“…K D = 952 nM vs. 285 nM. Compound 26 was previously studied using another BLI setup 16 with galectin immobilization on an NTA-type biosensor, and both K D values were comparable ( cf. 285 nM vs. 120 nM).…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…K D = 952 nM vs. 285 nM. Compound 26 was previously studied using another BLI setup 16 with galectin immobilization on an NTA-type biosensor, and both K D values were comparable ( cf. 285 nM vs. 120 nM).…”
mentioning
confidence: 99%
“…15 Our recent study with a simple inhibitor lactose demonstrated that a partial cone glycocalix[4]arene also acts as a strong inhibitor of Gal-3. 16 Generally, glycomimetics are better suited for galectin inhibition than natural carbohydrates due to their biostability and resistance to enzymatic degradation. 17 (Imino)coumaryl glycoconjugates were found to be strong galectin antagonists, 18 and 3- O -coumarylmethyl-disubstituted thiodigalactosides inhibited Gal-1/Gal-3 in a murine model of bleomycin-induced pulmonary fibrosis.…”
mentioning
confidence: 99%
See 3 more Smart Citations